Enterocin A-based antimicrobial film exerted strong antilisterial activity in sliced dry-cured ham immediately and after 6 months at 8 °C. (August 2022) - Aymerich, Teresa; Jofré, Anna; Bover-Cid, Sara
Abstract: To minimize the survival of Listeria monocytogenes on ready-to-eat (RTE)-products, active antimicrobial packaging based on polyvinyl alcohol films with Enterocin A or ethyl-lauroyl-arginate (LAE) have been designed and its antimicrobial activity assessed in vacuum-packed sliced dry-cured ham stored under refrigeration. The Enterocin A-based antimicrobial film exerted a strong antilisterial activity, causing an immediate reduction of L. monocytogenes counts of 1 log units compared with the control without antimicrobial. Besides, Enterocin A film enhanced (4-fold higher) the die-off rate along the 6 months of storage at 8 °C. The antilisterial effect of Enterocin A film applied on dry-cured ham complies with the performance criteria requirement of Alternative 1 of the US Listeria rule regarding the control of L. monocytogenes . Films made with LAE did not exert an immediate bactericidal effect but slightly increased the die-off rate of the pathogen and reduced its counts during the shelf life compared to the control batch. Highlights: Enterocin A-films exerted a strong antilisterial activity in dry-cured ham. Enterocin A-films could facilitate accomplishment of Listeria zero-policies. LAE-based films slightly increased die-off rate of L. monocytogenes.